Proceedings of the Arabic and Islamic sections of the 35th International Congress of Asian and North African Studies (ICANAS), Budapest, 1-7 July 1997. (Budapest Budapest)
2 c. (1. c. vii, 272 s. ; 2. c. vii, 300 s., [1] katlı sayfa nota)